2013
DOI: 10.1111/nph.12596
|View full text |Cite
|
Sign up to set email alerts
|

OsPT2, a phosphate transporter, is involved in the active uptake of selenite in rice

Abstract: Selenite is a predominant form of selenium (Se) available to plants, especially in anaerobic soils, but the molecular mechanism of selenite uptake by plants is not well understood.ltn1, a rice mutant previously shown to have increased phosphate (Pi) uptake, was found to exhibit higher selenite uptake than the wild-type in both concentration- and time-dependent selenite uptake assays. Respiratory inhibitors significantly inhibited selenite uptake in the wildtype and the ltn1 mutant, indicating that selenite upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
176
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(183 citation statements)
references
References 66 publications
(86 reference statements)
6
176
0
1
Order By: Relevance
“…SeO 3 2− is the primary form of selenite at pH 8.0, which may enter the plants through that an anion channels. However, Zhang et al (2014b) found that anion channel inhibitor could not significantly inhibit the absorption of selenite. This finding indicated that there are other pathways of selenite absorption in plants, which merit further study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…SeO 3 2− is the primary form of selenite at pH 8.0, which may enter the plants through that an anion channels. However, Zhang et al (2014b) found that anion channel inhibitor could not significantly inhibit the absorption of selenite. This finding indicated that there are other pathways of selenite absorption in plants, which merit further study.…”
Section: Discussionmentioning
confidence: 96%
“…Zhao et al (2010) revealed the molecular mechanism of Se absorption by the roots of rice through aquaporin family members, such as the silicon influx transporter OsNIP2;1 for H 2 SeO 3 and phosphate transporters for HSeO 3 − . Zhang et al (2014b) directly proved the involvement of a phosphate transporter in selenite absorption by expressing and mutating the phosphate transporter-encoding gene OsPT2. SeO 3 2− is the primary form of selenite at pH 8.0, which may enter the plants through that an anion channels.…”
Section: Discussionmentioning
confidence: 97%
“…NO, as a ubiquitous signaling molecule, has been extensively studied in plants ( Parani et al, ; Mur et al, ). Although Zhang et al () reported that higher transcription of OsPT2 resulted a significant enhancement of Se concentration of rice seedlings and Inostroza‐Blancheteau et al () found that the gene transcription of these sulfate transporters were enhanced after treatment with SeO 3 2− and then caused Se accumulation in wheat roots, they did not pay any attention to the role of NO. The present study is the first exploration on the role of NO in Se IV uptake and metabolism in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Sulphate addition to soil significantly increased levels of extractable selenate by decreasing selenate adsorption (Dhillon and Dhillon 2000;Sors et al 2005), and, subsequently sulfate inhibited selenate uptake through competition and regulation of sulphate transporters (Terry et al 2000;White et al 2004;Stroud et al 2010b). Similarly, the mechanism of phosphate inhibiting Se uptake has been identified (Li et al 2008;Zhang et al 2014b). In this study, phosphate and sulfate accumulated from 2007 to 2013 in topsoil due to application of basal fertilizer added in all treatments, but there was no significant difference between inorganic Nfertilizer and control treatments (Fig.…”
Section: Discussionmentioning
confidence: 38%